PENINGKATAN HASIL BELAJAR MENGGUNAKAN MEDIA KOMIK DIGITAL MATERI TOLERANSI DAN KOMPETISI KEBAIKAN - Asti Triasih (GURUKU, 2022)
The learning of students during the covid-19 pandemic in Islamic Religious Education (PAI) lessons requires teachers to be innovative in using the media to cultivate the value of truth and honesty better. The learning media used by teachers must support digital comics, namely illustrated stories. The purpose of this study is to make the learning outcomes of students better. The research subjects were students of class XI MIPA3 which totaled 35 people. The study was designed as many as two cycles, with data retrieval through pre-cycle observation. Data collection techniques in this study are tests, observations. Tests are used to obtain data on learning achievements. The data collection tool used is a test using question items / question instruments to measure student learning outcomes. And Observation uses observation sheets to measure the participation rate of learners. The results of the observations that have been carried out are analyzed descriptively comparatively, namely by comparing values between cycles and indicators in the study. Observation with descriptive analysis based on the results of observation and reflection of each cycle. The results of this study show that digital comic learning media has a positive impact in improving student learning outcomes. This can be seen from the better student learning outcomes on the material presented by the teacher (learning completion increases from pre-cycle, cycle I, and II, namely 31%, 57%, and 91%, respectively.